Data systems for the Linac Coherent Light Source. Issue 4 (27th July 2016) - Thayer, J.; Damiani, D.; Ford, C.; Gaponenko, I.; Kroeger, W.; O'Grady, C.; Pines, J.; Tookey, T.; Weaver, M.; Perazzo, A.
Abstract : The data acquisition and data management systems used at the Linac Coherent Light Source X‐ray free‐electron laser are described. Abstract : The data acquisition and data management systems for X‐ray free‐electron laser experiments at the Linac Coherent Light Source are described. These systems are designed to acquire and to reliably transport shot‐by‐shot data at a peak throughput of 5 GB s −1 to the offline data storage, where experimental data and the relevant metadata are archived and made available for user analysis. A case study of a serial femtosecond crystallography pipeline is presented.